Application of the Theory of Planned Behavior for Predicting the Intention of International Entrepreneurship: Global Mindset and Cultural Intelligence As Moderation Variables - Saputra, The Fennie; Sihombing, Sabrina (APMBA (Asia Pacific Management and Business Application), 2018)
International entrepreneurship is one of the wheels that contributes to the developmenet of emerging economy. In regards to the development of Indonesia. contributions were given in the form of providing employment, increasing state input, and strengthening foreign exchange reserves. Indonesia is one of the countries in ASEAN, which also supports international entrepreneurship by opening ASEAN international trade routes through the Asean Free Trade Area (AFTA). With the opening of international trade channels, business competition can be increased. Based on the results of a survey conducted by GEM on ASEAN in terms of international entrepreneurial intentions at the initial stage of business, Indonesia was estimated at 0.3%. Therefore this study will discuss more deeply about the factors that influence one's international entrepreneurial intentions which consist of attitudes, social norms, global mindset and cultural intelligence. This study used 200 respondents from one ot the wellknown university focusing on entrepreneural creation enrolled in entrepreneurship courses. Data analyzed using Moderated Multiple Regression (MMR) resulted a positive relationship between international behavioral control and entrepreneurial intentions where highly needed in creating successfull entrepreneur.